SOCIAL CONFLICT AS AN INDICATOR OF SOCIETAL DIGITAL TRANSFORMATION IN THE CONTEXT OF PUBLIC GOVERNANCE - Stadniichuk, Roman; Garafonova, Olga; Yankovoi, Roman; Efremov, Ilya; Artemov, Serhii (Socio-economic relations in the digital society, 2025)
The purpose of the article is to substantiate the theoretical foundations and develop a methodological approach to analyzing social conflict as an indicator of societal digital development, as well as to determine its role in shaping sustainable digital development strategies within the public governance system. The study established that the digital transformation of society creates new conditions for the emergence and escalation of social conflicts, which encompass economic, political, informational, and cultural spheres. Social conflicts in the digital environment arise due to unequal access to digital resources, algorithmic opacity, cybersecurity threats, manipulation in the information space, and violations of citizens' digital rights. The key results of the study include identifying the specific features of digital social conflicts, their causes, forms of manifestation, and socio-economic consequences for societal development. It was found that social conflicts in the digital environment can perform both destructive and constructive functions – either increasing social tension and societal polarization or stimulating the adaptation of social institutions to digital changes, updating digital policies, and fostering a digital culture of dialogue. A methodological approach to monitoring social conflicts as indicators of societal digital development has been proposed, enabling the identification of digital stability threats, the prediction of potential risks, and the formation of effective mechanisms for their resolution based on the principles of inclusiveness, transparency, and digital ethics. It is concluded that social conflicts are a natural component of a digital society and serve as an indicator of the level of digital maturity, social equality, and the effectiveness of state regulation in the field of digital transformation.
Keywords: social conflict; public governance; digital transformation; digital society; digital rights; digital inequality; information wars; digital governance; online protests; cybersecurity